Modern Student in the World of Mobile Devices - Grzegorz Kiedrowicz (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
The content of the study is to assess the use of the latest mobile devices associated with IT for the modern student. School system is in constant state of flux. The majority of teachers focus on the traditional presentation and enforcement of knowledge and skills, while the majority of students benefit greatly from the knowledge available virtually. It leads to the considerable gap and makes mutual communication and understanding more difficult.The same problems also occur in an academic environment. Research conducted among the students of the University of Technology and Humanities in Radom show the functioning of future teachers in the digital world.